Establishment of efficient method for callus culture and shoot regeneration of local Indian garlic (var. Yamuna safed) - Kapoor, Rashmi; Nasim, Sekh Abdul; Mahmooduzzafar, M.; Mujib, Abdul (Journal of Ecobiotechnology, 2012)
The experiment was designed to investigate the regeneration potentiality of a garlic variety (Yamuna Safed (G1)), and also to develop an efficient protocol for regeneration of garlic via callus culture. Higher percentage of callus was initiated from the combination of BAP and 2, 4 D at 2.0 mg/l and 0.25 mg/l respectively.Ã‚Â The hormone 2, 4-D, commonly used in tissue culture in garlic was found to be detrimental when used at the levels described in literatures. Rooting of individual shoots was induced after transfer to medium without growth regulator. The plantlets were established in the soil after acclimatization. Ã‚Â